A ética skinneriana e a tensão entre descrição e prescrição no Behaviorismo Radical - Castro, Marina Souto Lopes Bezerra de (Universidade Federal de São Carlos, 2007)
From the description of Skinner's theory since its beginning, we can understand the course which falls into ethical questions. Skinner asserts that the science of behavior can also be the science of values, that is, it can explain, it can describe, what we mean by values and what is being ethical, act in a way called ethical. Furthermore, the author argues that, from the radical behaviorism and its selection by consequences theory in the three levels, it is possible to elect a primary value, which can be the guide for somebody who engages in the project of cultural practices in a deliberated fashion. In this way, Skinner assumes a prescriptive attitude, as well as tries to reduce it to a descriptive scope. There it is a kind of tension in the Skinner's texts, because, besides describing the good of the culture, the author elects this value as the primary value. He tries to justify this election appeling to descriptive arguments, but, finally, he cannot find any "good reason". We assume that it is possible to originate ethical precepts from radical behaviorism, nevertheless radical behaviorism is not suficient to justify the choice of one or another precept. We cannot choose, only from its premises, the good of the culture, or the good of others, or the personal goods as the main value, since there are not enough arguments within the theory itself. If we want to explain why we choose this or that precept, on the point of view of the behavior analysis, we must look at the who-makes-the-choice history of contingencies.
Keywords: Behaviorismo (Psicologia); Skinner, Burrhus Frederick, 1904-1990; Ética; Valores; Radical behaviorism; Ethics; Values - goods; CIENCIAS HUMANAS::FILOSOFIA